Differences in patients derived from otolaryngology and other specialties with sleep apnea - Constanza Salas; Jorge Dreyse; Andrea Contreras; Gonzalo Nazar; Constanza Astorquiza; Rodrigo Cabezon; Gonzalo Labarca; Jorge Jorquera (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Snoring is a main concern in patients who consult an otolaryngologist (ENT physicians) and patients who have cardiovascular comorbidities or excessive daytime sleepiness who usually consult with other specialists. The aim of this study was to describe the clinical differences in patients with obstructive sleep apnea (OSA) referred from ENT or other specialists. Methods A prospective study was carried out between June 2015 and July 2018 in a tertiary center. We included patients with suspected OSA referred by the Home Sleep Apnea Test (HSAT) from different specialties such as ENT or other specialties. The main outcome measures of our study were demographic characteristics, clinical characteristics, sleep questionnaire results and HSAT results between OSA patients referred from ENT or other specialists. We used a t-test and chi-squared test for analysis. The diagnostic accuracy of the sleep questionnaires was achieved using receiver operating characteristic (ROC) curve and the area under the curve (AUC). Results A total of 481 patients were included. OSA was occurred in 82.4% of the subjects (90 in ENT and 306 in other specialties). Patients with OSA referred from other specialists were older than ENT patients (55 ± 13 vs 44 ± 12; p < 0.001), there was more obesity (IMC 31 ± 5.0 vs 28.7 ± 3.8; p < 0,001), a larger neck circumference (42.2 cm ± 3.7 vs 40.6 cm ± 3.0; p < 0.001) and more reported comorbidities (p < 0.001). ENT patients reported mild OSA (46% vs 31%, p = 0.015) and more positional apnea (62% vs 39%, p = 0.002). In this group, the STOP-BANG questionnaire showed an AUC 0.695 vs AUC 0.804, and for sensitivity, the best cutoff was 4 points. Patients referred from otorhinolaryngology are different from those referred from other specialties. Clinical evaluation and screening of OSA should be patient-centered according to these clinical findings.